Long term sequelae of sex steroid treatment in the management of constitutionally tall stature. Issue 4 (October 1995) - de Waal, W J; Torn, M; de Muinck Keizer-Schrama, S M; Aarsen, R S; Drop, S L
Abstract : AIM--To evaluate possible long term side effects of high doses of sex steroids in the management of constitutionally tall stature, with special attention to hypothalamic-gonadal function. METHODS--Sixty four tall adult men and 180 tall adult women, who received supraphysiological doses of sex hormones during puberty, were interviewed in a standardised way at a mean follow up period of 10 years after cessation of treatment. Sixty one untreated tall adult men and 94 untreated tall adult women served as controls. RESULTS--The majority of the subjects were satisfied with their decision regarding hormone treatment. Seventy seven per cent of the women and 78% of the men reported one or more side effects during treatment. Most side effects were mild. In women, only 3% stopped treatment because of an adverse event; in men, the reported side effects never stopped treatment. The frequency of reported side effects in women was higher during treatment with high doses of oestrogens than during oral contraceptive use, indicating a dose dependent relationship. Amenorrhoea of longer than six months after cessation of therapy was found in 5%. Menstrual cycle characteristics of previously treated women were comparable with controls. Malignancy was not reported. Information about a total of 127 pregnancies was obtained and revealed no distinct differences in details and outcome between previously treated women and men, and controls. CONCLUSIONS--At a mean follow up of 10 years there is no evidence that pharmacological doses of sex hormones have a long term effect on reproductive function. However, this period is still too short to draw definite conclusions.